Project Management: A Study in Organizational Conflict - Butler, Arthur G. (Academy of Management Journal, 1973)
Project management in functional organizations provides a fertile field for much-needed reexamination of the presumption of dysfunctional conflict when managers and employed professionals interact in organizations. Systematic analysis must indentify the foundations of human conflict and determine the extent to which the implications of such conflict for organizational behavior are functional or dysfunctional.